Antiparasitic Drugs in the United States—Two Roads to High Prices - Shahriar, Arman A.; Alpern, Jonathan D. (Frontiers in Sociology, 2020)
High prescription drug prices contribute significantly to healthcare spending in the United States and compromise patients’ access to quality medical care. A number of factors allow drug manufacturers to set much higher prices in the US than in other comparable high-income nations. Price-control depends primarily on the entry and persistence of generic products following the expiration of the market exclusivity period granted to the manufacturer of the brand name drug. Unfortunately, barriers to generic entry are common, allowing off-patent drugs like albendazole to remain relatively expensive despite having been marketed in the US for decades. By contrast, miltefosine became FDA approved more recently and has maintained a high price tag by way of a novel incentive program—the neglected tropical disease (NTD) priority review voucher (PRV) program. The voucher has a high market value and can be sold or transferred well before the drug for which it was awarded becomes available on the market. While both drugs are used to treat parasitic infections that are uncommon in the US, they differ by market and regulatory conditions—each telling an interesting pricing story.